Industrial applications of enzymes based on carbohydrate-based material - Gillian Eggleston (American Chemical Society, 2007)
This book provides an overall increase in awareness, understanding and implementation of the recent great advances in the production and application of industrail enzymes on carbohydrate materials. The field of industrial enzyme application has grown tremendously in the last ten years, because of the high specificity of enzymes to catalyze industrial processing reactions,the availablity of thousands of enzymes, and ,especially, the rapid growth of protein engineerign and genetically modified organismsto dramatically reduce production times and costs for new enzymes. Industrial enzymes also offer more environmentally friendly and scaleable industrial processes for the conversion of carbohydrate based materials into a diversity of value-added products, inculding the new 'biofuels'